Pengaruh Reflective Journaling Terhadap Tingkat Berpikir Kritis Mahasiswa Tahun Pertama Program Studi Ilmu Keperawatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan - Zulfa Hidayah; Kurnia Putri Yuliandari; Uki Noviana (PSIK FKKMK UGM, 2020)
Background: Nurses are required to continuously possess critical thinking skills in order to make rational decisions. One of the methods that can be employed to enhance nurses’ critical thinking abilities is through reflective journaling activities. Reflective journaling involves reflecting on and processing experiences, enabling the individual to solve problems when facing similar situations in the future. However, this practice is still relatively uncommon among nursing students.Objective: The aim of this study is to determine the influence of reflective journaling on the critical thinking abilities of first-year nursing students at Universitas Gadjah Mada (UGM).Method: This is a pre experimental research with a one group pretest-posttest design.The sample comprises all first-year nursing students from the 2019t at UGM. A total of 101 respondents were selected using purposive sampling based on inclusion criteria. The respondents engaged in reflective journaling activities six times over a period of six weeks. Data analysis was conducted using the Paired t-test.Outcome: The majority of respondents were female (93,3%) and had previously received information about reflective journaling activities (56,6%). The average score before the implementation of reflective journaling was 68,20 ± 2,336, while the average score after the intervention was 68,73 ± SD 3,218, with a p value of 0,091, indicating that there was no significant effect of the reflective journaling intervention.Conclusion: The study concludes that there is no significant influence of reflective journaling intervention on the critical thinking levels of first-year nursing students at UGM.ABSTRAKLatar belakang: Seorang perawat dituntut untuk senantiasa memiliki kemampuan berpikir kritis agar mampu membuat keputusan yang rasional. Salah satu metode yang dapat dilakukan untuk meningkatkan kemampuan berpikir kritis perawat adalah dengan kegiatan reflective journaling. Reflective journaling untuk merefleksikan dan memproses pengalaman sehingga dapat memecahkan masalah dalam menghadapi situasi serupa di masa mendatang masih jarang dilakukan pada mahasiswa keperawatan. Tujuan: mengetahui pengaruh reflective journaling terhadap kemampuan berpikir kritis pada mahasiswa keperawatan tahun pertama di Universitas Gadjah Mada (UGM).Metode: Penelitian ini merupakan penelitian pre-experimental dengan one group pretest-posttest design. Sampel penelitian adalah seluruh mahasiswa keperawatan tahun pertama angkatan 2019 di UGM. Pengambilan sampel dengan teknik purposive sampling didapatkan 101 responden sesuai dengan kriteria inklusi. Responden diberikan kegiatan reflective journaling sebanyak 6x selama 6 minggu. Analisis data yang digunakan adalah paired t-test dengan nilai p < 0,05.Hasil: Mayoritas responden berjenis kelamin perempuan (93,3%) dan sudah pernah memperoleh informasi terkait kegiatan reflective journaling (56,6%). Nilai rata-rata sebelum diberikan kegiatan reflective journaling (68,20 ± 2,336) dan nilai rerata setelah intervensi (68,73 ± 3,218) dengan nilai p = 0,091) yang menunjukkan tidak terdapat pengaruh intervensi reflective journaling. Kesimpulan: Tidak terdapat pengaruh yang signifikan antara intervensi reflective journaling terhadap tingkat berpikir kritis pada mahasiswa tahun pertama di PSIK FK-KMK UGM.